Annexin-coated particles induce antigen-specific immunosuppression. (17th February 2020) - Link, Corinna; Bujupi, Fatmire; Krammer, Peter H.; Weyd, Heiko
Abstract: Apoptotic cells mediate the development of tolerogenic dendritic cells (DC) and thus facilitate induction and maintenance of peripheral tolerance. Following the identification of the evolutionary conserved annexin core domain (Anx) as a specific signal on apoptotic cells which antagonises Toll-like receptor (TLR) signalling, we examined whether the tolerogenic capacity of Anx can be exploited to downregulate antigen-specific immune responses. The treatment of bone marrow-derived dendritic cells (BMDC) with particles harbouring Anx as well as the model antigen ovalbumin (OVA) attenuated the response of OVA-specific OT-II T cells. The co-culture of Anx-particle-treated DC and T cells resulted in an anergy-like phenotype characterized by reduced proliferation and cytokine secretion. Here we demonstrate that the anti-inflammatory effects of Anx which are mediated through DC can be used as a tool to generate a particle-based antigen delivery system that promotes antigen-specific immunosuppression. Such Anx-particles may be a new therapeutic approach for the treatment of autoimmune diseases.